Legal Certainty Of Aggregate Data Utilization In The Design Of Personal Data Protection Bill - Desi Ariani Sinulingga (Universitas Negeri Gorontalo, 2022)
The government has prepared Bill on Personal Data Protection (PDP Bill) that comprehensively regulates the personal data protection of society. One of the provisions in the PDP Bill, which is considered to be an obstacle in digital economy growth is an exclusion of the rights of Personal Data holders and the obligations of Personal Data processors for Aggregate Data, which are only intended for the purpose of state administration. As a result, the utilization of Aggregate Data for various purposes both research and business cannot be carried out by the community. In this study, a research method with the normative juridical and analytical descriptive approach is used that focuses on laws and regulations, and library materials such as literature and journals. The regulation of Aggregate Data in the PDP Bill is contrary to the theory and Aggregate Data rules in other countries, which argues that Aggregate Data is not Personal Data. Therefore, Aggregate Data as a whole is excluded or removed from the regulation of Personal Data Protection, whether intended for the Government interest or other purposes.